Per- and polyfluoroalkyl substances, vitamin D, and risk of preterm birth in a Canadian cohort - Mandy Fisher; James Owen; Leonora Marro; Beth Potter; Hope A. Weiler; Gillian England-Mason; Michael M. Borghese; Mark Walker; Linda Dodds; Michael Helewa; Tye E. Arbuckle; Bruce Lanphear; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Predicting Attrition in a Public Nutrition Education Program: A Machine Learning Approach - Rohini Daraboina; Andrea Leschewski; Andrew Simpson; Gemma Bastian; Semhar Michael; George Langelett; Stacey Finkelstein (Journal of Nutrition Education and Behavior, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A phylogenetic perspective on the performance of Lactococcus lactis as starter culture in milk and plant milks - Zheng Zhao; Yuxin Zhang; David J. Simpson; Michael G. Gänzle (Food Research International, 2025)

Calcite priming of a hydrothermal eruption at South Orakonui, Ngā Tamariki Geothermal Field, New Zealand - Mark P. Simpson; Michael D. Rosenberg; Cristian Montanaro; Duncan J. Graham (Journal of Volcanology and Geothermal Research, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Diet quality in relation to serum perfluoroalkyl substance concentrations in Canadian preadolescents - Ashlyn Simpson; Mandy Fisher; Stéphanie Harrison; Anne-Sophie Morisset; Michael M. Borghese; Joseph M. Braun; Maryse F. Bouchard; Trisha Saha; Constadina Panagiotopoulos; Linda Booij; Katherine Morrison; Jillian Ashley-Martin (Environmental Research, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Physiological response of milkfish ( Chanos chanos ) to capture in a fly fishing catch‐and‐release recreational fishery - Andy J. Danylchuk; Lucas P. Griffin; Michael Lawrence; Sascha Clark Danylchuk; Eleanor Brighton; Gail Fordham; George Curd; Kyle Simpson; Devan Vd Merwe; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Recreational angling for novel marine species and related tourism development can be important in a Blue Economy. The milkfish ( Chanos chanos ) is growing in popularity as a target of fly fishing‐based catch‐and‐release (C&R) recreational fisheries, largely because of their challenge to catch and powerful swimming abilities, resulting in fight times that can exceed 1 h. Anecdotal sentiments by anglers claim that milkfish can fight for long periods of time because they do not accumulate blood lactate. To test this hypothesis, we measured blood lactate and blood glucose for 21 milkfish caught by fly fishing in the remote Alphonse Group of islands, Republic of Seychelles. Fight times ranged 5–78.3 min. Blood lactate and blood glucose concentrations increased with fight times that did not exceed 60 min. Total length of milkfish was not correlated to blood lactate or blood glucose concentrations. Ours is the first study on C&R of milkfish that debunks the anecdote that milkfish can fight for long periods of time because they do not accumulate blood lactate. Our study also revealed that milkfish may begin to physiologically recover after fight times longer than 60 min. In the context of C&R, our study indicates that anglers should limit fight times to 20–30 min when possible to reduce angling‐induced physiological stress and other potential impacts (e.g., depredation) on milkfish in recreational fisheries.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Strain-level identification of bacteria persisting in food and in food processing facilities: when do two isolates represent the same strain and which tools identify a strain? - Vi D Pham; David J Simpson; Michael G Gänzle (Current Opinion in Food Science, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

LA-ICP-Q-MS/MS ReOs geochronology: A comparison of N2O and CH4 reaction gases - Alexander Simpson; Stijn Glorie; Sarah Gilbert; Renée Tamblyn; Michael G. Gadd (Chemical Geology, 2024)

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

The role of dissolved organic carbon in Great Smoky Mountains National Park streams impacted by long-term acid deposition - Jason R. Brown; John S. Schwartz; Michael E. Essington; Qiang He; Matt A. Kulp; Ian M. Simpson (Environmental Monitoring and Assessment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Leveraging wastewater surveillance to detect viral diseases in livestock settings - Warish Ahmed; Yawen Liu; Wendy Smith; Wayne Ingall; Michael Belby; Aaron Bivins; Paul Bertsch; David T. Williams; Kirsty Richards; Stuart Simpson (Science of The Total Environment, 2024)

Crustal architecture and tectonic development of western Queensland, Australia, based on deep seismic reflection profiling: Implications for Proterozoic continental assembly and dispersal - Russell J. Korsch; Michael P. Doublier; Dominic D. Brown; Janelle M. Simpson; Andrew J. Cross; Ross D. Costelloe; Wenping Jiang (Tectonophysics, 2024)

Olfactory tract/bulb metal concentration in Manganese-exposed mineworkers - Luis F. Gonzalez-Cuyar; Gill Nelson; Susan Searles Nielsen; Wendy W. Dlamini; Amelia Keyser-Gibson; C. Dirk Keene; Michael Paulsen; Susan R. Criswell; Natalie Senini; Lianne Sheppard; Shar Samy; Christopher D. Simpson; et al. (NeuroToxicology, 2024)

Bioprotective lactobacilli in Crescenza and Gouda cheese models to inhibit fungal spoilage - Zheng Zhao; David J. Simpson; Michael G. Gänzle (International Dairy Journal, 2024)

Environmental DNA highlights the influence of salinity and agricultural run-off on coastal fish assemblages in the Great Barrier Reef region - Aashi Parikh; Johan Pansu; Adam Stow; Michael St J. Warne; Christine Chivas; Paul Greenfield; Frédéric Boyer; Stuart Simpson; Rachael Smith; Jacob Gruythuysen; Geoffrey Carlin; Natalie Caulfield; et al. (Environmental Pollution, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Evaluation of Orthotrichum lyellii moss as a biomonitor of diesel exhaust - Christopher Zuidema; Michael Paulsen; Christopher D. Simpson; Sarah E. Jovan (Science of The Total Environment, 2024)

IncobotulinumtoxinA in the Treatment of Musician’s Focal Hand Dystonia: A Placebo-Controlled, Crossover Trial - David Simpson; Alexandra Nmashie; Mary Catherine George; Chuanjie Wu; Alexander Pantelyat; Eckart Altenmüller; Michael Chen; David Feng; Steven J Frucht (Toxicon, 2024)

A large scale temporal and spatial environmental DNA biodiversity survey of marine vertebrates in Brazil following the Fundão tailings dam failure - Rose Lines; Manjeeti Juggernauth; Georgia Peverley; James Keating; Tiffany Simpson; Mahsa Mousavi-Derazmahalleh; Michael Bunce; Tina E. Berry; Alice Taysom; Angelo F. Bernardino; Phillip Whittle (Marine Environmental Research, 2023)

Distinct dynamics of plant- and microbial-derived soil organic matter in relation to varying climate and soil properties in temperate agroecosystems - Meiling Man; Edward G. Gregorich; Michael H. Beare; Benjamin H. Ellert; Myrna J. Simpson (Geochimica et Cosmochimica Acta, 2023)

Modulating Cortical Hemodynamic Activity in Parkinson’s Disease Using Focal Transcranial Direct Current Stimulation: A Pilot Functional Near-infrared Spectroscopy Study - Michael W Simpson; Margaret Mak (Brain Topography, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Compositional changes in the humin fraction resulting from the long-term cultivation of an Irish grassland soil: Evidence from FTIR and multi-NMR spectroscopies - Guixue Song; Andre J. Simpson; Michael H.B. Hayes (Science of The Total Environment, 2023)

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

Fine-scale variability in coral bleaching and mortality during a marine heatwave - Shreya Yadav; Ty N. F. Roach; Michael J. McWilliam; Carlo Caruso; Mariana Rocha de Souza; Catherine Foley; Corinne Allen; Jenna Dilworth; Joel Huckeba; Erika P. Santoro; Renee Wold; Jacquelyn Simpson; et al. (Frontiers in Marine Science, 2023)
Coral bleaching and mortality can show significant spatial and taxonomic heterogeneity at local scales, highlighting the need to understand the fine-scale drivers and impacts of thermal stress. In this study, we used structure-from-motion photogrammetry to track coral bleaching, mortality, and changes in community composition during the 2019 marine heatwave in Kāneʻohe Bay, Hawaiʻi. We surveyed 30 shallow reef patches every 3 weeks for the duration of the bleaching event (August-December) and one year after, resulting in a total of 210 large-area, high-resolution photomosaics that enabled us to follow the fate of thousands of coral colonies through time. We also measured environmental variables such as temperature, sedimentation, depth, and wave velocity at each of these sites, and extracted estimates of habitat complexity (rugosity R and fractal dimension D) from digital elevation models to better understand their effects on patterns of bleaching and mortality. We found that up to 80% of corals experienced moderate to severe bleaching in this period, with peak bleaching occurring in October when heat stress (Degree Heating Weeks) reached its maximum. Mortality continued to accumulate as bleaching levels dropped, driving large declines in more heat-susceptible species (77% loss of Pocillopora cover) and moderate declines in heat-tolerant species (19% and 23% for Porites compressa and Montipora capitata , respectively). Declines in live coral were accompanied by a rapid increase in algal cover across the survey sites. Spatial differences in bleaching were significantly linked to habitat complexity and coral species composition, with reefs that were dominated by Pocillopora experiencing the most severe bleaching. Mortality was also influenced by species composition, fractal dimension, and site-level differences in thermal stress. Our results show that spatial heterogeneity in the impacts of bleaching are driven by a mix of environmental variation, habitat complexity, and differences in assemblage composition.

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Comparing environmental DNA collection methods for sampling community composition on marine infrastructure - Jason B. Alexander; Michael J. Marnane; Justin I. McDonald; Sherralee S. Lukehurst; Travis S. Elsdon; Tiffany Simpson; Shawn Hinz; Michael Bunce; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2023)

Diphenhydramine-Induced Antimuscarinic Delirium Treated with Physostigmine and Transdermal Rivastigmine - James D. Whitledge; C. James Watson; Michael Simpson; Azza Bakkar; Leora Boussi; Michael Scott; Katherine L. Boyle (Journal of Medical Toxicology, 2023)

Contrasting Effects of Nitrogen Addition on Leaf Photosynthesis and Respiration in Black Mangrove in North Florida - Matthew A. Sturchio; Jeff Chieppa; Lorae T. Simpson; Ilka C. Feller; Samantha K. Chapman; Michael J. Aspinwall (Estuaries and Coasts, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Warfarin Overdose in an Adolescent Not Dependent on Anticoagulation: Reversal Strategy and Kinetics - C. James Watson; Michael D. Simpson; James D. Whitledge; Al Patterson; Michele M. Burns (Journal of Medical Toxicology, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Articles You Might Have Missed - James Whitledge; Michael Simpson; C. James Watson; Michele Burns (Journal of Medical Toxicology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The quorum‐sensing systems of Vibrio campbellii DS40M4 and BB120 are genetically and functionally distinct - Chelsea A. Simpson; Blake D. Petersen; Nicholas W. Haas; Logan J. Geyman; Aimee H. Lee; Ram Podicheti; Robert Pepin; Laura C. Brown; Douglas B. Rusch; Michael P. Manzella; Kai Papenfort; Julia C. van Kessel (Environmental Microbiology, 2021)
Summary Vibrio campbellii BB120 (previously classified as Vibrio harveyi ) is a fundamental model strain for studying quorum sensing in vibrios. A phylogenetic evaluation of sequenced Vibrio strains in Genbank revealed that BB120 is closely related to the environmental isolate V. campbellii DS40M4. We exploited DS40M4's competence for exogenous DNA uptake to rapidly generate greater than 30 isogenic strains with deletions of genes encoding BB120 quorum‐sensing system homologues. Our results show that the quorum‐sensing circuit of DS40M4 is distinct from BB120 in three ways: (i) DS40M4 does not produce an acyl homoserine lactone autoinducer but encodes an active orphan LuxN receptor, (ii) the quorum regulatory small RNAs (Qrrs) are not solely regulated by autoinducer signalling through the response regulator LuxO and (iii) the DS40M4 quorum‐sensing regulon is much smaller than BB120 (~100 genes vs. ~400 genes, respectively). Using comparative genomics to expand our understanding of quorum‐sensing circuit diversity, we observe that conservation of LuxM/LuxN proteins differs widely both between and within Vibrio species. These strains are also phenotypically distinct: DS40M4 exhibits stronger interbacterial cell killing, whereas BB120 forms more robust biofilms and is bioluminescent. These results underscore the need to examine wild isolates for a broader view of bacterial diversity in the marine ecosystem.

Small-scale spatial structure affects predator-prey dynamics and coexistence - Anudeep Surendran; Michael J. Plank; Matthew J. Simpson (Theoretical Ecology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Small-scale spatial structure influences large-scale invasion rates - Michael J. Plank; Matthew J. Simpson; Rachelle N. Binny (Theoretical Ecology, 2020)

Soil phosphorus pools with addition of fertiliser phosphorus in a long-term grazing experiment - Timothy I. McLaren; Ronald J. Smernik; Michael J. McLaughlin; Therese M. McBeath; Malcolm R. McCaskill; Fiona A. Robertson; Richard J. Simpson (Nutrient Cycling in Agroecosystems, 2020)

The endangered White's seahorse Hippocampus whitei chooses artificial over natural habitats - Michael Simpson; Rebecca L. Morris; David Harasti; Ross A. Coleman (Journal of Fish Biology, 2019)
To explore whether the endangered White's seahorse Hippocampus whitei would choose to inhabit artificial over natural habitats, 10 adult H. whitei individuals were put through a series of binary choice trials in aquaria, during which they were offered different paired combinations of natural (different types of macroalga and seagrass) and artificial habitat (panels of swimming‐net material). It was found that H. whitei displayed a significant choice for swimming‐net material over all other available natural habitats and chose habitats according to the following rankings: (a) Net; (b) Sargassum sp.; (c) Posidonia australis ; (d) Zostera muelleri. Hippocampus whitei ’s choice of swimming net material over natural habitat suggests that these artificial structures could be a useful conservation measure for seahorses in areas where natural habitat is becoming less favourable due to declines in abundance or quality.

Closing the global ozone yield gap: Quantification and cobenefits for multistress tolerance - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Michael Frei; Kent Burkey; Lisa Emberson; Johan Uddling; Malin Broberg; Zhaozhong Feng; Kazuhiko Kobayashi; Madhoolika Agrawal (Global Change Biology, 2018)
Increasing both crop productivity and the tolerance of crops to abiotic and biotic stresses is a major challenge for global food security in our rapidly changing climate. For the first time, we show how the spatial variation and severity of tropospheric ozone effects on yield compare with effects of other stresses on a global scale, and discuss mitigating actions against the negative effects of ozone. We show that the sensitivity to ozone declines in the order soybean > wheat > maize > rice, with genotypic variation in response being most pronounced for soybean and rice. Based on stomatal uptake, we estimate that ozone (mean of 2010–2012) reduces global yield annually by 12.4%, 7.1%, 4.4% and 6.1% for soybean, wheat, rice and maize, respectively (the “ozone yield gaps”), adding up to 227 Tg of lost yield. Our modelling shows that the highest ozone‐induced production losses for soybean are in North and South America whilst for wheat they are in India and China, for rice in parts of India, Bangladesh, China and Indonesia, and for maize in China and the United States. Crucially, we also show that the same areas are often also at risk of high losses from pests and diseases, heat stress and to a lesser extent aridity and nutrient stress. In a solution‐focussed analysis of these results, we provide a crop ideotype with tolerance of multiple stresses (including ozone) and describe how ozone effects could be included in crop breeding programmes. We also discuss altered crop management approaches that could be applied to reduce ozone impacts in the shorter term. Given the severity of ozone effects on staple food crops in areas of the world that are also challenged by other stresses, we recommend increased attention to the benefits that could be gained from addressing the ozone yield gap.

Phaseolus vulgaris lectins: A systematic review of characteristics and health implications - Shudong He; Benjamin K. Simpson; Hanju Sun; Michael O. Ngadi; Ying Ma; Tiemin Huang (Critical Reviews in Food Science and Nutrition, 2018)

Advanced Backcross Quantitative Trait Loci (QTL) Analysis of Oil Concentration and Oil Quality Traits in Peanut (Arachis hypogaea L.) - Jeffrey N. Wilson; Ratan Chopra; Michael R. Baring; Michael Gomez Selvaraj; Charles E. Simpson; Jennifer Chagoya; Mark D. Burow (Tropical Plant Biology, 2017)

Enhancing climate change adaptation: strategies for community engagement and university-community partnerships - James S. Gruber; Jason L. Rhoades; Michael Simpson; Latham Stack; Leslie Yetka; Robert Wood (Journal of Environmental Studies and Sciences, 2017)

Stormwater management and climate change: vulnerability and capacity for adaptation in urban and suburban contexts - Trisha L. Moore; John S. Gulliver; Latham Stack; Michael H. Simpson (Climatic Change, 2016)

The fate of fertiliser P in soil under pasture and uptake by subterraneum clover – a field study using 33P-labelled single superphosphate - Timothy I. McLaren; Michael J. McLaughlin; Therese M. McBeath; Richard J. Simpson; Ronald J. Smernik; Christopher N. Guppy; Alan E. Richardson (Plant and Soil, 2016)

Enigmatic spheres from the Upper Triassic Lockatong Formation, Newark Basin of eastern Pennsylvania: evidence for microbial activity in marginal-lacustrine strandline deposits - Edward L. Simpson; David L. Fillmore; Michael J. Szajna; Emily Bogner; Margariete G. Malenda; Kelsey M. Livingston; Brian Hartline (Palaeobiodiversity and Palaeoenvironments, 2015)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Long‐term changes in organic matter and mercury transport to lakes in the sporadic discontinuous permafrost zone related to peat subsidence - Jennifer B. Korosi; Jamylynn McDonald; Kristen A. Coleman; Michael J. Palmer; John P. Smol; Myrna J. Simpson; Jules M. Blais (Limnology and Oceanography, 2015)
Permafrost‐supported peatlands near the southern limit of permafrost are experiencing dramatic landscape changes as a result of recent climate warming, which have the potential to impact aquatic ecosystems through changes in terrestrial run‐off. Our objectives were to determine how terrestrial organic matter inputs to aquatic ecosystems in the southern Northwest Territories (Canada) changed as a result of peat subsidence, and whether terrestrial organic matter can be linked to sedimentary mercury. To accomplish this, we analyzed lipid biomarkers, lignin‐derived phenols, and other geochemical proxies in sediment cores from two lakes (KAK‐1 and TAH‐7) affected by recent peat subsidence. Both lakes experienced substantial shifts in organic matter proxies through time, but the trajectory of change differed, reflecting local heterogeneity in hydrological setting and other environmental factors. In KAK‐1, recent peat subsidence corresponded to a decrease in lignin‐derived phenol yield, increased inferred lignin oxidation, and δ 15 N depletion. In TAH‐7, peat subsidence was likely initiated by a local forest fire, and resulted in an increase in the n ‐alkanol ratio C 30 /(C 30 + C 28 ) (consistent with a warmer, wetter climate), lignin‐derived phenol yield (mainly syringyls), and δ 13 C depletion. In TAH‐7, total mercury inputs were positively correlated to terrestrial carbon inputs, suggesting allochthonous carbon is an important vector for mercury transport to the lake. In both lakes, an increase in the C 23 /(C 23 + C 29 ) n ‐alkane ratio was observed and suggests increased organic matter input from Sphagnum mosses. Our results demonstrate how terrestrial landscape changes occurring as a result of peat subsidence can influence carbon accumulation in aquatic ecosystems in discontinuous permafrost zones.

Next-generation transcriptome sequencing, SNP discovery and validation in four market classes of peanut, Arachis hypogaea L. - Ratan Chopra; Gloria Burow; Andrew Farmer; Joann Mudge; Charles E. Simpson; Thea A. Wilkins; Michael R. Baring; Naveen Puppala; Kelly D. Chamberlin; Mark D. Burow (Molecular Genetics and Genomics, 2015)

Nutritional ecology beyond the individual: a conceptual framework for integrating nutrition and social interactions - Mathieu Lihoreau; Camille Buhl; Michael A. Charleston; Gregory A. Sword; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2015)
Over recent years, modelling approaches from nutritional ecology (known as Nutritional Geometry) have been increasingly used to describe how animals and some other organisms select foods and eat them in appropriate amounts in order to maintain a balanced nutritional state maximising fitness. These nutritional strategies profoundly affect the physiology, behaviour and performance of individuals, which in turn impact their social interactions within groups and societies. Here, we present a conceptual framework to study the role of nutrition as a major ecological factor influencing the development and maintenance of social life. We first illustrate some of the mechanisms by which nutritional differences among individuals mediate social interactions in a broad range of species and ecological contexts. We then explain how studying individual‐ and collective‐level nutrition in a common conceptual framework derived from Nutritional Geometry can bring new fundamental insights into the mechanisms and evolution of social interactions, using a combination of simulation models and manipulative experiments.

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Early response of the northeast subarctic Pacific plankton assemblage to volcanic ash fertilization - Josiane Mélançon; Maurice Levasseur; Martine Lizotte; Pierre Delmelle; Jay Cullen; Roberta C. Hamme; Angelica Peña; Kyle G. Simpson; Michael Scarratt; Jean-Éric Tremblay; Jie Zhou; Keith Johnson; et al. (Limnology and Oceanography, 2014)
Fe‐poor water collected at Sta. P20 in the Gulf of Alaska in June 2011 was enriched with different concentrations of volcanic ash (0.12, 1.2, and 10 mg L ‒1 ) from two subduction zone volcanoes, Kasatochi and Chaiten, and incubated onboard under in situ conditions for 6 d. The experimental setup also included a control (no addition) and a positive control (addition of 0.6 nmol L ‒1 FeSO 4 ). Following a 4 d lag period, there were increases in carbon fixation rates (up to a factor of 10) and chlorophyll a concentrations (up to a factor of 3) in the positive control and in the ash‐enriched (1.2 and 10 mg L ‒1 ) treatments. Diatoms dominated at the end of the incubations, but cyanobacteria, dinoflagellates, pelagophytes, and haptophytes were also stimulated by the presence of ash. Deposition of ∼ 1 mg ash L ‒1 , which is in the lower range of those estimated to have caused the August 2008 bloom following the eruption of the Kasatochi volcano in the Aleutian Islands, would suffice to trigger a bloom in the Gulf of Alaska.

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Arthropod food webs become increasingly lipid‐limited at higher trophic levels - Shawn M. Wilder; Michael Norris; Raymond W. Lee; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2013)
Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Practical considerations for conducting ecotoxicity test methods with manufactured nanomaterials: what have we learnt so far? - Richard D. Handy; Nico van den Brink; Mark Chappell; Martin Mühling; Renata Behra; Maria Dušinská; Peter Simpson; Jukka Ahtiainen; Awadhesh N. Jha; Jennifer Seiter; Anthony Bednar; Alan Kennedy; et al. (Ecotoxicology, 2012)
This review paper reports the consensus of a technical workshop hosted by the European network, NanoImpactNet (NIN). The workshop aimed to review the collective experience of working at the bench with manufactured nanomaterials (MNMs), and to recommend modifications to existing experimental methods and OECD protocols. Current procedures for cleaning glassware are appropriate for most MNMs, although interference with electrodes may occur. Maintaining exposure is more difficult with MNMs compared to conventional chemicals. A metal salt control is recommended for experiments with metallic MNMs that may release free metal ions. Dispersing agents should be avoided, but if they must be used, then natural or synthetic dispersing agents are possible, and dispersion controls essential. Time constraints and technology gaps indicate that full characterisation of test media during ecotoxicity tests is currently not practical. Details of electron microscopy, dark-field microscopy, a range of spectroscopic methods (EDX, XRD, XANES, EXAFS), light scattering techniques (DLS, SLS) and chromatography are discussed. The development of user-friendly software to predict particle behaviour in test media according to DLVO theory is in progress, and simple optical methods are available to estimate the settling behaviour of suspensions during experiments. However, for soil matrices such simple approaches may not be applicable. Alternatively, a Critical Body Residue approach may be taken in which body concentrations in organisms are related to effects, and toxicity thresholds derived. For microbial assays, the cell wall is a formidable barrier to MNMs and end points that rely on the test substance penetrating the cell may be insensitive. Instead assays based on the cell envelope should be developed for MNMs. In algal growth tests, the abiotic factors that promote particle aggregation in the media (e.g. ionic strength) are also important in providing nutrients, and manipulation of the media to control the dispersion may also inhibit growth. Controls to quantify shading effects, and precise details of lighting regimes, shaking or mixing should be reported in algal tests. Photosynthesis may be more sensitive than traditional growth end points for algae and plants. Tests with invertebrates should consider non-chemical toxicity from particle adherence to the organisms. The use of semi-static exposure methods with fish can reduce the logistical issues of waste water disposal and facilitate aspects of animal husbandry relevant to MMNs. There are concerns that the existing bioaccumulation tests are conceptually flawed for MNMs and that new test(s) are required. In vitro testing strategies, as exemplified by genotoxicity assays, can be modified for MNMs, but the risk of false negatives in some assays is highlighted. In conclusion, most protocols will require some modifications and recommendations are made to aid the researcher at the bench.

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

A palaeolimnological meta-database for assessing the ecological status of lakes - Richard W. Battarbee; David Morley; Helen Bennion; Gavin L. Simpson; Michael Hughes; Viktorija Bauere (Journal of Paleolimnology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Isolation and fractionation of soil humin using alkaline urea and dimethylsulphoxide plus sulphuric acid - Guixue Song; Michael H. B. Hayes; Etelvino H. Novotny; Andre J. Simpson (The Science of Nature, 2011)

Adiaspiromycosis Due to Emmonsia crescens is Widespread in Native British Mammals - Andrew M. Borman; Vic R. Simpson; Michael D. Palmer; Christopher J. Linton; Elizabeth M. Johnson (Mycopathologia, 2009)

Toward increasing avian diversity: urban wildscapes programs - Amanda L. Aurora; Thomas R. Simpson; Michael F. Small; Kelly C. Bender (Urban Ecosystems, 2009)

ERP correlates of anticipatory attention: spatial and non-spatial specificity and relation to subsequent selective attention - Corby L. Dale; Gregory V. Simpson; John J. Foxe; Tracy L. Luks; Michael S. Worden (Experimental Brain Research, 2008)

Nectin-1/HveC Mediates herpes simplex virus type-1 entry into primary human sensory neurons and fibroblasts - Scott A Simpson; Michael D Manchak; Elizabeth J Hager; Claude Krummenacher; J Charles Whitbeck; Myron J Levin; Curt R Freed; Christine L Wilcox; Gary H Cohen; Roselyn J Eisenberg; Lewis I. Pizer (Journal of NeuroVirology, 2005)

Molecular structures and associations of humic substances in the terrestrial environment - André J. Simpson; William L. Kingery; Michael H. Hayes; Manfred Spraul; Eberhard Humpfer; Peter Dvortsak; Rainer Kerssebaum; Markus Godejohann; Martin Hofmann (The Science of Nature, 2002)

Revised nomenclature for strain 129 mice - Michael F.W. Festing; Elizabeth M. Simpson; Muriel T. Davisson; Larry E. Mobraaten (Mammalian Genome, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Uptake of 26-Al and 67-Ga into brain and other tissues of normal and hypotransferrinaemic mice - Aleksandar Radunovic´; Fukiko Ueda; Kishor B. Raja; Robert J. Simpson; Jill Templar; Samantha J. King; John S. Lilley; J. Philip Day; Michael W.B. Bradbury (BioMetals, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Chloropropionic acid-induced alterations in glucose metabolic status: possible relevance to cerebellar granule cell necrosis - Edward A. Lock; Andrew Gyte; Peter Widdowson; Michael Simpson; Ian Wyatt (Archives of Toxicology, 1995)